Hepatitis B among female sex workers in Ribeirão Preto - São Paulo, Brazil Hepatite B entre mulheres profissionais do sexo em Ribeirão Preto - São Paulo, Brasil - Afonso Dinis Costa Passos; José Fernando de Castro Figueiredo; Ana de Lourdes Candolo Martinelli; Márcia Guimarães Villanova; Margarida Pásseri do Nascimento; Ana Maria Coimbra Gaspar; Clara Fumiko Tachibana Yoshida (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2007)
OBJECTIVE: To estimate the prevalence of hepatitis B markers and to study the risk factors for this disease among female sex workers in the city of Ribeirão Preto, Brazil. METHODS: A questionnaire was given to 449 female sex workers in order to obtain information about demographic, socioeconomic and behavioral variables. Blood samples were collected and analyzed by immunoenzymatic techniques for detection of HBsAg, anti-HBs, anti-HBc and anti-HCV markers. RESULTS: The mean age of participants was 23 years, varying from 13 to 64 years. A high spatial mobility was observed, with 47.9% of participants residing in places out of the region of Ribeirão Preto or in other Brazilian states. Complete absence of previous vaccine against hepatitis B was referred by 98.2%. Overall, the presence of any hepatitis B marker was observed in 106 participants (prevalence of 23.6%; 95% CI: 19.7 27.5), with 84 positive for anti-HBs (18.7%), 100 for anti-HBc (22.3%), and only 3 for HBsAg (0.7%). The logistic regression analysis showed association between hepatitis B markers and the following co-variables: residence in Ribeirão Preto, age, low socioeconomic level, consumption of crack, intercourse with HIV-infected individuals, history of previous hepatitis, intercourse with a case of hepatitis, and positivity for hepatitis C. CONCLUSIONS: Ribeirão Preto's female sex workers present several risk factors for hepatitis B and almost absence of previous specific vaccination, making it necessary to emphasize this low-cost preventive measure, preferably through the use of a mobile team, taking the vaccine to their places of work. OBJETIVOS: Estimar a prevalência de marcadores de hepatite B e estudar os fatores de risco para esta doença entre mulheres profissionais do sexo na cidade de Ribeirão Preto, Brasil. MÉTODOS: Foi aplicado um questionário a 449 mulheres profissionais do sexo, com a finalidade de levantar informações demográficas, socioeconômicas e comportamentais. Amostras de sangue das participantes foram analisadas através de técnicas imunoenzimáticas, para detecção dos marcadores HBsAg, anti-HBs e anti-HBc. RESULTADOS: A idade média das participantes foi 23 anos, variando de 13 a 64 anos. Uma elevada mobilidade espacial foi verificada, com 47,9% delas residindo em locais fora da região de Ribeirão Preto ou em outros estados brasileiros. Completa ausência de vacinação prévia contra hepatite B foi referida por 98,2%. No total, observou-se presença de qualquer marcador de hepatite B em 106 participantes (prevalência de 23,6%; IC95%: 19,7 27,5), com 84 positivos para anti-HBs (18,7%), 100 para anti-HBc (22,3%) e apenas 3 para HBsAg (0,7%). A análise por regressão logística evidenciou associação entre marcadores de hepatite B e as seguintes co-variáveis: idade, baixo nível socioeconômico, consumo de crack, relações sexuais com indivíduos infectados pelo HIV, história de hepatite prévia, relações sexuais com pessoas portadoras de hepatite e positividade para hepatite C. CONCLUSÕES: As profissionais do sexo em Ribeirão Preto apresentam diversos fatores de risco para hepatite B e quase total ausência de vacinação prévia específica, tornando necessários esforços concentrados na aplicação dessa medida de baixo custo, preferencialmente através do uso de equipes móveis que levem a vacina até os seus locais de trabalho.